Implementasi Manajemen Pembiayaan Pendidikan di SMK Informatika Bina Generasi 3 Kabupaten Bogor - Muhammad Hidayat Ginanjar; Edi Purwanto (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2022)
A successful educational institution cannot be separated from the support of high educational costs, because in essence the quality of education will be directly proportional to the education costs incurred, the higher and more expensive the education costs used and spent, the better the educational services and able to produce graduates. Qualified graduates with high learning outcomes. It seems that it will be difficult to realize a good quality of education if it is not supported by the high cost of education. This paper presents the results of research on financial management of education at SMK Informatika Bina Generasi 3 Bogor. This research was conducted at SMK Informatika Bina Generasi 3 Bogor using a qualitative approach. Data collection techniques through observation and interviews. The implementation of educational financial management includes: (1) Financial budget planning, (2) Financial management implementation, (3) Financial management evaluation